Reckless abandon - Woods, Stuart (New York : Signet Book, 2004)
Cop-turned-attorney Stone Barrington joins forces with Holly Barker, the tenacious female police chief of Orchid Island, Florida, when she comes to Manhattan to pursue a fugitive from her jurisdiction.
Keywords: Private investigators -- New York (State) -- New York -- Fiction; Detective and mystery fiction